1994
DOI: 10.1021/j100085a014
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of H2 and Prototypical Solvent Molecules with Cr(CO)5 in the Gas Phase

Abstract: Transient infrared spectroscopy has been used to study reactions of Cr(C0)s generated by UV (35 1 or 355 nm) photolysis of Cr(C0)6 in the gas phase. At 298 K Cr(C0)5 reacts with H2, C2H4, CzF4, and C6H6 with bimolecular rate constants of (9.0 f 2.9), (19.0 f 2.0), (1.8 f 0.2), and (26.0 f 1.0) X 10-l' cm3 molecule-I s-l, respectively, where the rate constants reported are for the high-pressure limit. Infrared absorptions attributed to Cr(CO)5L where L = Hz, C2H4, CzF4, and C6H6 were observed. The rate of disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
52
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 10 publications
14
52
1
Order By: Relevance
“…The ⌬H ‡ value (30 Ϯ 2 kJ⅐mol Ϫ1 ) for the reaction of 2 with CO can be used as a lower limit for the WOCH 4 binding enthalpy in scCH 4 . It is interesting to compare this result with previous calculations (30), which predict a WOCH 4 interaction of 18 kJ⅐mol Ϫ1 , and with gas-phase TRIR experiments, which estimate a CrOCH 4 bond-dissociation energy of 33 Ϯ 8 kJ⅐mol Ϫ1 (26). Clearly, there is a significant WOCH 4 interaction in solution at room temperature.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…The ⌬H ‡ value (30 Ϯ 2 kJ⅐mol Ϫ1 ) for the reaction of 2 with CO can be used as a lower limit for the WOCH 4 binding enthalpy in scCH 4 . It is interesting to compare this result with previous calculations (30), which predict a WOCH 4 interaction of 18 kJ⅐mol Ϫ1 , and with gas-phase TRIR experiments, which estimate a CrOCH 4 bond-dissociation energy of 33 Ϯ 8 kJ⅐mol Ϫ1 (26). Clearly, there is a significant WOCH 4 interaction in solution at room temperature.…”
supporting
confidence: 56%
“…TRIR measurements on Cr(CO) 6 in the gas phase demonstrated that photolysis produces Cr(CO) 5 . In the presence of CH 4 (600 torr; 1 torr ϭ 133 Pa), a 2-fold decrease in the rate of regeneration of Cr(CO) 6 was interpreted to indicate a weak interaction between the Cr(CO) 5 fragment and CH 4 , with an estimated binding enthalpy for CrOCH 4 of 33 Ϯ 8 kJ⅐mol Ϫ1 (26). We recently have used a combination of supercritical fluids and TRIR spectroscopy to characterize a series of organometallic noble gas complexes at room temperature (11), leading to the characterization of Re( i PrCp)(CO)(PF 3 )Xe by NMR (27).…”
mentioning
confidence: 99%
“…Table 1 lists the dissociation energies D e and D 0 of the H 2 ligand. The D 0 value for 1 a of 15.9 kcal/mol calculated at the CCSD(T) level is in very good agreement with the experimental value obtained by Weitz and coworkers (15.0 ± 1.3 kcal/mol) [43]. An estimation of the H 2 bond energy in 1 c (W(CO) 5 (H 2 )) gave D 0 > 16 kcal/mol [44], again in good agreement with our calculated CCSD(T) value of 16.3 kcal/mol.…”
Section: Resultssupporting
confidence: 90%
“…Other TRIR experiments monitoring the photolysis of Cr(CO) 6 in the gas phase detected a transient species, assigned to be Cr(CO) 5 (CH 4 ) [72]. Another TRIR study did not directly detect the presence of Cr(CO) 5 (CH 4 ), following the photolysis of Cr(CO) 6 in the presence of a low pressure (11.4 psi) of CH 4 and this work reported an estimation of the binding energy of the Cr(CO) 5 (CH 4 ) bond (33 (±8) kJ mol −1 ) [74].…”
Section: Organometallic Complexes Of the Lighter Alkanesmentioning
confidence: 61%